2017
DOI: 10.1080/17565529.2017.1291408
|View full text |Cite
|
Sign up to set email alerts
|

Farmers and policy-makers’ perceptions of climate change in Ethiopia

Abstract: Reference:Hameso, Seyoum (2017) The study forms part of the broader research project into actual and perceived climate change that included climate data (see Hameso, 2015) and book chapter on farmers perceptions about climate change (Hameso, 2014) but this paper reports on and compares climate change as perceived by farmers and policy makers. I acknowledge comments from two anonymous reviewers.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 26 publications
4
23
0
Order By: Relevance
“…There are misconceptions related to climate change in Ethiopia. These include, but are not limited to, attribution of the cause of climate change to the will of God as well as weakened indigenous practices (Ayal & Leal Filho, 2017;Hameso, 2017). In the study areas, there were participants who indicated that climate changes because of the wrong deeds of human beings in respecting their culture, as a result of which God penalizes them by denying rainfall.…”
Section: High Risk Perception Profilementioning
confidence: 99%
See 1 more Smart Citation
“…There are misconceptions related to climate change in Ethiopia. These include, but are not limited to, attribution of the cause of climate change to the will of God as well as weakened indigenous practices (Ayal & Leal Filho, 2017;Hameso, 2017). In the study areas, there were participants who indicated that climate changes because of the wrong deeds of human beings in respecting their culture, as a result of which God penalizes them by denying rainfall.…”
Section: High Risk Perception Profilementioning
confidence: 99%
“…We also used a holistic approach to measure the latent constructs constituting the framework. Many studies defined perception by focusing on an increase or decrease in temperature and/or rainfall (Deressa et al, 2011;Hameso, 2017;Lasco et al, 2016). Although it gives valuable insights, the observation of changes in temperature and rainfall shows only an awareness of climate change (Duinen et al, 2015;Gebrehiwot & Van Der Veen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…David-Chavez and Gavin [49] developed indicators for assessing responsible community engagement and identified patterns in levels of community engagement. Based on their experience and knowledge, indigenous people used indicators to interpret natural surroundings and predict both short-and long-term seasonal processes [29,50]. Besides the scientific value, indicators and TEK were incorporated in the adjustment with environmental changes [21,27,50], and in developing priorities for adaptive strategies [23,28].…”
Section: Tek Based Observationsmentioning
confidence: 99%
“…Most of the researches on adaptation to climate change have been focused on tropics and lowland (e.g., Ghana, Zimbabwe and Brazil) [11,21,27]. Recently, documenting the traditional knowledge of aboriginal mountainous communities (e.g., alpine Himalaya region, Ethiopia and Tanzania) [15,[28][29][30] was considered an essential task. under the higher climate changing rate and harsher environmental condition, communities in high mountains have been and will be affected by climate change compared with those living in lowland areas [31].…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study in Tanzania (Dejene et al, 1997) also reported significant differences on how small-scale farmers perceived land degradation in their fields compared to the perception of extension workers. A recent study in Ethiopia (Hameso, 2018) found sharp differences in the way farmers perceive climate change causes from those of policy makers. Contrarily to the results in Chapter 4, in Western Kenya distant communities of farmers did not differ in their perceptions when it came to describing factors which caused soil fertility decline (Odendo et al, 2010).…”
Section: Implication To Science and Societymentioning
confidence: 95%